Efficient use of liquid digestate in microalgae cultivation for high biomass production and nutrient recovery - Akkaya, Ebru; Can-Guven, Emine (IWA PUBLISHING, 2022)
In this study, different pre-treatment methods were applied to liquid digestate (LD) for the growth of the mixed microalgal culture. In addition, nutrient removal in the LD was investigated. Dilution, filtration, and centrifugation were applied as pre-treatment methods. Microalgal growth was evaluated as dry weight (DW) and nutrient removal was investigated with the analysis of ammonium (NH4+-N) and phosphate (PO4-3-P). Microalgal DW constantly increased throughout the experiment and reached the maximum values of 4.24, 4.02, and 1.47 g/L in centrifuged, diluted, and filtered medium, respectively. Maximum NH4+ (97.7%) and PO4-3 (50.4%) removal efficiency was observed in the centrifuged LD. Based on the results of this study, the optimum growth medium for microalgal growth was centrifuged LD but this culture can be cultivated in diluted LD up to 40-fold. Results also showed that using LD for microalgae production is a suitable application for both nutrient supply for microalgal growth and nutrient recovery from LD.
Keywords: anaerobic digestion; biogas; microalgal growth; nitrogen; phosphorus; MUNICIPAL WASTE-WATER; FED-BATCH CULTIVATION; ANAEROBIC DIGESTATE; DESMODESMUS SP; REMOVAL; CHLORELLA; GROWTH; EFFLUENT; OPTIMIZATION; ARTHROSPIRA; Engineering; Environmental Sciences & Ecology; Water Resources